ANALISIS OPTIMALISASI KONTRIBUSI ENERGI PLTS PADA SISTEM HIBRIDA PLTS–MIKROHIDRO 500 W UNTUK PENERANGAN JALAN UMUM AREA PERKEBUNAN DI KELURAHAN TARATARA - Runtuewene, Miracle Marqiano Johanes; Mamusung, Christo; Mantow, Michelle Bianca; Langie, Maureen; Noya, Donald Bastian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The integration of solar photovoltaic (PV) generation into a hybrid energy system introduces an inherent challenge: the intermittent nature of solar irradiance often produces unstable power output, particularly under cloudy or rainy conditions. This study analyses the optimisation of PV energy contribution in a 500 W hybrid PV–microhydro system supplying a public street lighting (PJU) load in the plantation area of Taratara Village, Tomohon City. A prototype combining a 250 Wp polycrystalline PV module and an undershot waterwheel coupled to a permanent magnet generator was designed, fabricated, and tested. Time-series data were collected for solar irradiance, water discharge, output voltage, current, and real power under varying weather conditions. The data were used to map the correlation between irradiance fluctuation and PV conversion efficiency, and to compute the percentage of PV contribution to the total daily energy generated. Projected results indicate that PV contributes around 15–17% of the total daily energy on clear days and drops to 5–6% on overcast days, while the microhydro generator delivers a stable baseload of approximately 250 W throughout the day. The study recommends an MPPT-based dispatch strategy and a battery sizing of at least 100 Ah at 12 V to ensure load continuity. The findings can serve as a technical reference for future deployment of hybrid renewable street lighting in similar rural plantation areas.